The use of desmos-assisted creative problem-solving learning in improving critical thinking skills - Septian, Cepi; Firmansyah, Eka; Rakhmat, Rizki Safari; Kariadinata, Rahayu (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
The low students' mathematical critical thinking ability in one of the high schools in Bandung City is a problem that requires teachers to develop and implement innovative learning approaches. Various previous studies have shown that creative learning and encouraging active involvement of students can improve critical thinking skills. This study uses a mixed method with an embedded design type, especially an embedded experimental design model, and adopts a pretest-posttest control group design. The purpose of this study is to examine the effectiveness of the Desmos-assisted Creative Problem Solving (CPS) learning model in improving students' mathematical critical thinking skills. The population of this study is high school students in the city of Bandung, with a purposive sampling technique to select two classes as a sample. The instruments used included mathematical critical thinking ability tests, observation sheets, and interview guidelines. The results of the data analysis showed that the improvement in mathematical critical thinking skills of students who obtained Desmos-assisted CPS learning was higher compared to students in the control class. Therefore, the Desmos-assisted CPS learning model is effectively used in an effort to improve students' mathematical critical thinking skills, especially in social studies classes students, and can be used as an alternative approach to learning mathematics in schools. This research is expected to contribute to the development of mathematics education, especially in the integration of technology with innovative learning models to encourage students' critical thinking skills.